(untitled) (Verba Vitae Unwira, 2020)
One of the cultural assets of people of Gorontalo is Language diversity. However, it is unfortunate to mention that manyurban Gorontalo people nowadays are mostly less proficient speakers of Gorontalo local language. It is elderly people instead ofyoung people who still show better proficiency in using the language. The young people seem insecure and embarrassed in using the language in their daily social interactions.This study intends to examine the dynamics of the use of Gorontalo local languages ??in the communication activities of Gorontalo ethnic groups, especially the Talumelito community. This research uses a qualitative-descriptive approach. The results show that the use of the Gorontalo local language in communication activities by the Talumelito communitiesis unequal. This is confirmed by the data indicating that: 1) The Talumelito communities still use local language vocabulary for place names and events, 2) In general the Talumelitocommunities, except for the ones who reside in hamlets 1 and 3, still use local languages ??in their communication activities. 3) The minimal use of regional languages ??is mainly found in communication activities among young people.This of course will affect the process of preserving the local language in the Talumelito community.The government and the communitiesin Talumelitohave endorsed the use local language in cultural events or festivals as well as at schools.